Human Amnion Epithelial Cell Therapy for Chronic Liver Disease - Neil Andrewartha; George Yeoh (Hindawi Limited, 2019)
Liver fibrosis is a common consequence of chronic liver disease. Over time, liver fibrosis can develop into liver cirrhosis. Current therapies for liver fibrosis are limited, and liver transplant is the only curative therapy for patients who progress to end-stage disease. A potential approach to treat chronic liver disease with increasing interest is cell-based therapy. Among the multiple cell types which have been proposed for therapeutic uses, human amnion epithelial cells and amniotic fluid-derived mesenchymal cells are promising. These cells are highly abundant, and their use poses no ethical concern. Furthermore, they exert potent anti-inflammatory and antifibrotic effects in animal models of liver injury. This review highlights the therapeutic characteristics and discusses how human amnion epithelial cells can be utilised as a therapeutic tool for chronic liver disease.